Endoplasmic Reticulum Stress Activates Unfolded Protein Response Signaling and Mediates Inflammation, Obesity, and Cardiac Dysfunction: Therapeutic and Molecular Approach - Amen, Omar Mohammed; Sarker, Satyajit D.; Ghildyal, Reena; Arya, Aditya (Frontiers in Pharmacology, 2019)
Obesity has been implicated as a risk factor for insulin resistance and cardiovascular diseases (CVDs). Although the association between obesity and CVD is a well-established phenomenon, the precise mechanisms remain incompletely understood. This has led to a relative paucity of therapeutic measures for the prevention and treatment of CVD and associated metabolic disorders. Recent studies have shed light on the pivotal role of prolonged endoplasmic reticulum stress (ERS)-initiated activation of the unfolded protein response (UPR), and the ensuing chronic low-grade inflammation, and altered insulin signaling in promoting obesity-compromised cardiovascular system (CVS). In this aspect, potential ways of attenuating ERS-initiated UPR signaling seems a promising avenue for therapeutic interventions. We review intersecting role of obesity-induced ERS, chronic inflammation, insulin resistance, and oxidative stress in the discovery of targeted therapy. Moreover, this review highlights the current progress and strategies on therapeutics being explored in preclinical and clinical research to modulate ERS and UPR signaling.